Role of microbial granules in biological wastewater treatment - Xu, Bin. (2008)
Microorganisms are almost always found in naturally occurring aggregates, such as suspended floes, granules and attached biofilms. As compared with biofilms, microbial granules contain similarly high concentrations of biomass and high microbial diversity, but they are dense aggregates without any carriers. Meanwhile they also differ from suspended floes in both physical properties and microbial arrangement. As opposed to floes, granular sludge is better able to cope with high and fluctuating loading rates by uncoupling hydraulic retention time from the sludge retention time. The rapid settling velocities of granules can also result in a reduction in the size of reactors, as well as negate the use of large and costly settling tanks. So far, the anaerobic granulation process has been successfully exploited to treat a variety of industrial wastewaters for over twenty years, and more than 900 anaerobic granular sludge units have been operated worldwide.